Sekuritisasi pendatang tanpa izin (PTI) di Sabah - Ramli, Dolah (2018)
This study utilizes the applicability of the securitization framework in understanding migrants as a security issue in Sabah. Although migrants as a security threat has been discussed extensively by local and international scholars, most of the studies are dominated by the mainstream approach primarily, Realism. Therefore, this study provides an alternative in understanding the relationship between migrant issues and security threat in Sabah using the securitization theory. Two cases are presented to examine the securitization of immigrants in Sabah. First, ‘all out war against illegal’ and Ops Nyah II, (2002-03) and second, Ops Nasihat, 2004-05. This study is conducted to achieve four objectives including to examine migrants as security issues in Sabah using securitization theory; to analyze social constructivism approach as an alternative in explaining migrants as a security issue; to understand the interactions between actors-audience in securitization of immigrants issues in Sabah, and to examine factors affecting the degree of violence and government policies in addressing the issue of immigrants in Sabah. This study employs qualitative approach by combining several research methods including text/discourse analysis, documents analysis (such as government reports, archives, major newspapers) interviews with key respondents, and fieldwork observations. The main findings of this study suggests that, immigrant as a threat to security is not a pre-given but a product of social process that is developed through language or known as “speech act”. Apparently, even though securitization actors successfully convinced the audience and subsequently made immigrants a security issue, the state implements different policies in addressing the same issue, namely immigrants. Therefore, this study reveals that the securitization of immigrants in Sabah requires the shift from an exclusive focus of discursive practice, to a more realistic understanding of the domestic and international factors affecting the state’s policies. As such, language per se is inadequate in understanding and explaining the reality of the immigrants and relevant governmental policies in Sabah.